2016
DOI: 10.18488/journal.82/2016.3.1/82.1.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Emissions, Urbanization and Population: Empirical Evidence in Sub Saharan Africa

Abstract: Urbanization and population have been viewed as two of the major contributors to global CO 2 emissions. This paper aims at examining empirically the relationship between urbanization, population and CO 2 emissions in 45 Sub-Saharan African (SSA) countries. This goal was achieved by using a panel data from 1990-2010 and the newly established pooled mean group (PMG) estimator for dynamic heterogeneous panels. This study is a contribution to the empirics of climate change which has been an ongoing debate over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 4 publications
2
10
0
1
Order By: Relevance
“…Tiwari et al (2022) found a positive relationship between trade openness and CO 2 emissions in India. Adusah-Poku (2016) reported similar findings for a study of Sub-Saharan African countries. Abokyi et al (2021) employed the ARDL model to study the role of trade openness in electricity consumption and carbon emissions in Ghana.…”
Section: Related Literaturesupporting
confidence: 82%
See 2 more Smart Citations
“…Tiwari et al (2022) found a positive relationship between trade openness and CO 2 emissions in India. Adusah-Poku (2016) reported similar findings for a study of Sub-Saharan African countries. Abokyi et al (2021) employed the ARDL model to study the role of trade openness in electricity consumption and carbon emissions in Ghana.…”
Section: Related Literaturesupporting
confidence: 82%
“…Grossman & Krueger (1991) first explored the empirical relationship between trade and emissions, categorizing the effects into scale, technique, and composite. Subsequent studies on the environmental effect of trade have reported ambiguous findings (Adusah-Poku, 2016;and Kwakwa et al, 2019). Tiwari et al (2022) found a positive relationship between trade openness and CO 2 emissions in India.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that growing urbanization and population could lower CO2 emissions significantly in the short and long run. Moreover, it was concluded that CO2 emissions grew faster due to energy use in more populated countries like Nigeria and Ethiopia than in less populated countries like Cape Verde and Equatorial Guinea (Poku, 2016). Katircioglu studied the environmental Kuznets curve (EKC) and the oil price effect on that in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ongoing environmental degradation has placed numerous countries under pressure to decrease CO 2 e and to focus on low-carbon emitter economies. As a result, many small and large series of agreements, such as the "Paris Agreement, " "Kyoto Protocol, " and the "United Nations Framework Convention on Climate Change" (UNFCCC) have been made among different developing and developed countries to control and decrease CO 2 e. The reduction of CO 2 e has become important in recent years because many industrialized and developed countries have applied their policies to mitigate Co 2 e (Zhang et al, 2014;Adusah-Poku, 2016;Yang et al, 2017). However, the ongoing concerns for sustainable development have increased over the years as the quality of the environment has declined because of economic activities.…”
Section: Introductionmentioning
confidence: 99%